PEMBATALAN MEREK AKIBAT TIDAK DIPENUHINYA SYARAT IKTIKAD BAIK DALAM PENDAFTARAN MEREK (ANALISIS PUTUSAN PENGADILAN NIAGA MEDAN NOMOR 01/2013/MEREK/PN.NIAGA MEDAN) - KHAIRI AFIF NASUTION (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. SAIDIN 2. T.KEIZERINA DEVI A 3. JELLY LEVIZA A brand is one of the intellectual property components which need specificattention since there are still violations against it. This is related to fraudulentbusiness behavior which needs competitive and profit oriented efforts that bringsabout an opportunity for fraudulent and illegal business. Moreover, a person’smotivation to violate against the use of brand is to get advantages in his businesspractice.Keywords: Dispute, Brand, Bad Faith